Outcropping reef ledges drive patterns of epibenthic assemblage diversity on cross-shelf habitats - Monk, J.; Barrett, N.; Hill, N.; Lucieer, V.; Nichol, S.; Siwabessy, Justy; Williams, S. (2016)
Seafloor habitats on continental shelf margins are increasingly being the subject of worldwide conservation efforts to protect them from human activities due to their biological and economic value. Quantitative data on the epibenthic taxa which contributes to the biodiversity value of these continental shelf margins is vital for the effectiveness of these efforts, especially at the spatial resolution required to effectively manage these ecosystems. We quantified the diversity of morphotype classes on an outcropping reef system characteristic of the continental shelf margin in the Flinders Commonwealth Marine Reserve, southeastern Australia. The system is uniquely characterized by long linear outcropping ledge features in sedimentary bedrock that differ markedly from the surrounding low-profile, sand-inundated reefs. We characterize a reef system harboring rich morphotype classes, with a total of 55 morphotype classes identified from the still images captured by an autonomous underwater vehicle. The morphotype class Cnidaria/Bryzoa/Hydroid matrix dominated the assemblages recorded. Both a and ß diversity declined sharply with distance from nearest outcropping reef ledge feature. Patterns of the morphotype classes were characterized by (1) morphotype turnover at scales of 5 to 10s m from nearest outcropping reef ledge feature, (2) 30 % of morphotype classes were recorded only once (i.e. singletons), and (3) generally low levels of abundance (proportion cover) of the component morphotype class. This suggests that the assemblages in this region contain a considerable number of locally rare morphotype classes. This study highlights the particular importance of outcropping reef ledge features in this region, as they provide a refuge against sediment scouring and inundation common on the low profile reef that characterizes this region. As outcropping reef features, they represent a small fraction of overall reef habitat yet contain much of the epibenthic faunal diversity. This study has relevance to conservation planning for continental shelf habitats, as protecting a single, or few, areas of reef is unlikely to accurately represent the geomorphic diversity of cross-shelf habitats and the morphotype diversity that is associated with these features. Equally, when designing monitoring programs these spatially-discrete, but biologically rich outcropping reef ledge features should be considered as distinct components in stratified sampling designs.